Weeds. Season one - Dannelly, Brian; Perkins, Elizabeth, 1960-; Parker, Mary-Louise; Nealon, Kevin, 1953- (Santa Monica, CA : Lionsgate, 2006)
In order to care for her children and maintain her standard of living, a young woman becomes her wealthy neighborhood's pot dealer after her husband's sudden death.
You can't miss the bear -- Free goat -- Good shit lollipop -- Fashion of the Christ -- Lude awakening -- Dead in the nethers -- Higher education -- The punishment light -- The punishment lighter -- The godmother.
Features: Smoke and mirrors original marijuana mockumentary, Smokey snippets, six commentaries with cast and crew, Showtime original content including special on suburbia, Agrestic herbal recipes, music video: "More than a friend" by All too much, interactive menus.
Elizabeth Perkins, Mary-Louise Parker, Kevin Nealon.
Originally broadcast on Showtime television in 2005.
TV rating: TV-MA.
DVDs, Dolby digital 5.1 surround.
In English with optional English or Spanish subtitles.
Keywords: Widows -- Drama; Fatherless families -- Drama; Drug dealers -- Drama; Marijuana -- Drama; Video recordings for the hearing impaired; Fiction television programs; Comedy television programs